2009
DOI: 10.1111/j.1600-0447.2008.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of course of disability in antipsychotic‐treated and untreated schizophrenia patients

Abstract: Disability in untreated schizophrenia patients remains unchanged over time. Treatment with antipsychotics in the community results in a considerable reduction in disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 21 publications
0
49
1
Order By: Relevance
“…Medication and treatment adherence is a big barrier in treating psychiatric illness like schizophrenia,[10] as most patients do have insight about their illness. Further the nature of schizophrenia itself, where patients experience negative symptoms,[11] may make it difficult for them to attend the yoga treatment consistently for the required period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Medication and treatment adherence is a big barrier in treating psychiatric illness like schizophrenia,[10] as most patients do have insight about their illness. Further the nature of schizophrenia itself, where patients experience negative symptoms,[11] may make it difficult for them to attend the yoga treatment consistently for the required period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study of schizophrenia patients in rural south India, Thirthalli et al ., compared the outcome in patients who did versus did not receive treatment, and found that the disability was clearly better in those who received treatment. [33] In a controlled study, Kulhara et al .,[34] showed that structured psychoeducational intervention was significantly better than routine outpatient care on several outcome indices. Early interventions are therefore feasible and acceptable in low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients classified as "disabled" declined significantly in the treated group, but remained the same in the untreated group (Thirthalli et al 2009). …”
mentioning
confidence: 90%